Investigation on the feasibility of eliminating harmonic excitation signal en-route to performing experimental modal analysis (EMA) under operational condition - Jannifar, A.; Zubir, Mohd Nashrul Mohd; Kazi, Salim Newaz; Zulkifli, Nurin Wahidah Mohd; Ahmad, Norhafizan (Springer Verlag (Germany), 2018)
This study focuses on introducing a criteria for conducting harmonic excitation signal elimination as well as investigating its effectiveness towards achieving complete isolation of harmonic disturbance in performing EMA under operational condition. By modulating the ratio between harmonic excitation and impact knocking frequencies, it was revealed that the harmonic signal was efficiently attenuated with sufficient number of averaging blocks. The results highlighted close agreement between simulation and experimental approaches with maximum deviation of 2 %, under specific design criteria. It was determined that a non-periodic triggering frequency significantly affect the elimination performance in terms of trend and amplitude reduction. This work underlines the importance of controlling the triggering frequency to yield the desired design criteria for achieving rapid and highly efficient elimination of harmonic excitation signal. The results have proven that the proposed technique can be further adapted to isolate the harmonic in conventional EMA conducted under operational condition.